METHODOLOGY OF USING THE GOOGLE CLASSROOM MOBILE APPLICATION IN TEACHING INFORMATICS AND INFORMATION TECHNOLOGIES FOR SECONDARY SCHOOL STUDENTS - Rasulov Inom Muydinovich (Journal Park Publishing, 2022)
This article discusses how to use the Google classroom mobile application in teaching computer science and information technology to secondary school students. Mastering the school course of informatics is designed to ensure that students become familiar with modern trends in the development of ICT not only at the theoretical level, but also in practice.
Keywords: pedagogy; informatics; information technology